2016
DOI: 10.1159/000446108
|View full text |Cite
|
Sign up to set email alerts
|

Omphalocele-Exstrophy-Imperforate Anus-Spinal Defects Complex: Associated Malformations in 12 New Cases

Abstract: Objective: The omphalocele-exstrophy-imperforate anus-spinal defects (OEIS) complex is a rare variant of the bladder exstrophy epispadias complex with in most cases unknown etiology. Due to the rarity of the disease, no large series exist that describe the prenatal spectrum of disease or additional malformations. Methods: In this study, we present the prenatal findings in a series of 12 cases. Results: All fetuses showed exstrophy of the bladder, 9/12 omphalocele, 9/12 anal atresia, 10/12 neural tube defects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
0
14
0
5
Order By: Relevance
“…A vertebral malformation associated with renal malformations, tracheoesophageal fistula, cardiac malformations, and limb defects should raise concern with a VACTERL association [21] . OEIS (omphalocele-exstrophy-imperforate anusspinal defect) complex is a rare variant of the bladder exstrophy-epispadias complex that can include sacral anomaly, which can be prenatally diagnosed [22] . We observed that spinal cord anomalies were present in 14/19 cases of sacral malformations.…”
Section: Discussionmentioning
confidence: 99%
“…A vertebral malformation associated with renal malformations, tracheoesophageal fistula, cardiac malformations, and limb defects should raise concern with a VACTERL association [21] . OEIS (omphalocele-exstrophy-imperforate anusspinal defect) complex is a rare variant of the bladder exstrophy-epispadias complex that can include sacral anomaly, which can be prenatally diagnosed [22] . We observed that spinal cord anomalies were present in 14/19 cases of sacral malformations.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of sacral agenesis with epispadias are rare and should prompt a search for other signs of the OEIS complex, which is a rare variant of the bladder exstrophy epispadias complex and which, in most cases, is of unknown etiology and in which spinal defects can include sacral anomalies …”
Section: Item 7: Systematic Analysis Of the Genitourinary Tractmentioning
confidence: 99%
“…5,23,60 Cases of sacral agenesis with epispadias are rare and should prompt a search for other signs of the OEIS complex, 2 which is a rare variant of the bladder exstrophy epispadias complex and which, in most cases, is of unknown etiology and in which spinal defects can include sacral anomalies. 66,67 In conclusion, parents should be informed of the risk of lower urinary tract dysfunction during childhood. Prenatal care and planning can be helpful for initiating an early urologic evaluation and limiting the risk of hydronephrosis or vesicoureteral reflux.…”
Section: Item 7: Systematic Analysis Of the Genitourinary Tractmentioning
confidence: 99%
“…In the prenatal setting, hydro(metro)colpos typically presents as a retrovesical, sometimes septate hypoechogenic mass with accumulation of debris within the cyst within the lower fetal abdomen. Differential diagnosis of intraabdominal cystic masses most often is difficult and includes hydronephrosis, fetal ovarian cysts, anterior cystic teratoma, cloacal malformation [1], megacystis with lower urinary tract obstruction [2], hepatic cysts [3], fetal sacrococcygeal teratoma [4], anterior meningocele, and hydro(metro)colpos.…”
Section: Introductionmentioning
confidence: 99%